Brewing Service Quality into Cambodia Public Transportation - Ung, Veasna (Archives of Business Research, 2019)
This has prompted the transportation sector in Cambodia to pay more and more attention in assessing the overall passengers’ perceived service quality that has been viewed as a “foundation” of passenger satisfaction. This paper aims to identify components of service quality of Cambodian bus transport service. This research was conducted by descriptive in nature and uses multiple regression to identify the most important factors of passenger satisfaction with the augmented SERVQUAL model and additional two dimensions (culture, and safety and efficiency) which researcher named new model of RACTERS (Reliability, Assurance, Culture, Tangibility, Empathy, Responsiveness, Safety &efficient). Using cross-sectional data with a sample of 698 respondents, the estimation results found that five dimensions (safety and efficient, assurance, empathy, culture and tangibility) have a significant and positive impact on the overall passenger satisfaction, with safety and efficiency dimension being the most important predictor of passenger’s satisfaction.